Museums Toured (Raton, NM Raton Range, 1979)
This article is about Museums in Raton and Cimarron being visited as part of a survey of area museums.
Newspaper article
Master list item #: 73
File location is in the Raton file Cabinet
Keywords: Nakamura, Phillip -- Museum of New Mexico Coordinator; Bennett, Charles -- Museum of New Mexico Educatio Division; Lanz, John -- Artist; Museum of New Mexico -- Santa Fe; Santa Fe Trail Museum -- Springer, New Mexico; Museum Tours; Museum Programing; Local Museums; Springer, New Mexico; Cimarron, New Mexico; Raton, New Mexico